Wpływ stylów przywiązania na rozwój zaburzeń jedzenia u dzieci i nastolatków - Abdo , Areej (Studia Edukacyjne, 2017)
This article seeks to examine the relationship between attachment styles in childhood and the development of eating disorders later in life. The assumption underlying the article is, the development of the social structure places considerable emphasis on eating as a way of socialization and a comfortable experience. A review of the research literature on the field documents a positive relationship between eating disorders, health problems and difficulties in family and interpersonal relationships.1 Therefore, it can be said that the assumption that the relationship between the attachment style of parents and children and eating is justified, since personal coping habits, especially attachment styles, are expressed to a certain extent in the specific eating behavior of the individual.